Propuesta de un Producto eco-turístico basado en el “Cóndor Andino” (Vultur gryphus) en las parroquias de Saraguro y San Antonio de Cumbe del Cantón Saraguro, Provincia de Loja. - Flores Gualán, Neicer Jefferson (2024)
Eco-tourism is a key tool to conserve the environment, promote sustainable development, generate income for local communities and raise awareness about the importance of protecting biodiversity and world cultures. In this context, the focus of this research is on the conservation of the Andean Condor through eco-tourism, an activity that is developed responsibly to protect both the species and its fragile environment. The presence of the Condor in Parishes of Saraguro Canton has made it possible to propose the design of an eco-tourism product based on the “Andean Condor” (Vultur gryphus) in the parishes of Saraguro and San Antonio de Cumbe, Canton Saraguro, Loja province. To achieve this objective, two specific objectives were established: to diagnose the eco-tourism potential and the current situation of the Andean Condor in the parishes and the proposal of the eco-tourism product. The methodology used began with the biophysical diagnosis of the study area, for the tourism system the manual for Local Tourism Diagnosis. Interviews were also conducted with experts in wildlife to determine the current situation of the Andean Condor, 384 surveys were applied to define the ecotourist people’s profile, and Geographic Information Systems (GIS) were used to create the corresponding maps. For the ecotourism products, the methodological procedure for product design was used to facilitate new tourism entrepreneurs and the manual for the development of tourism routes and itineraries of the Ministry of Tourism (MINTUR). Among the main results include four products; two routes and two eco-tourism circuits focused on the sightseeing and conservation of the Andean Condor and its fragile environment, 13 attractions with potential ecotourism, and three key sightseeing points for the species. The study highlights the potential ecotourism of the species, proposing routes and circuits for its conservation and enjoyment.